Actin-associated Proteins in the Pathogenesis of Podocyte Injury - He, Fang-Fang; Chen, Shan; Su, Hua; Meng, Xian-Fang; Zhang, Chun (Current Genomics, 2013)
Podocytes have a complex cellular architecture with interdigitating processes maintained by a precise organization of actin filaments. The actin-based foot processes of podocytes and the interposed slit diaphragm form the final barrier to proteinuria. The function of podocytes is largely based on the maintenance of the normal foot process structure with actin cytoskeleton. Cytoskeletal dynamics play important roles during normal podocyte development, in maintenance of the healthy glomerular filtration barrier, and in the pathogenesis of glomerular diseases. In this review, we focused on recent findings on the mechanisms of organization and reorganization of these actin-related molecules in the pathogenesis of podocyte injury and potential therapeutics targeting the regulation of actin cytoskeleton in podocytopathies.
Keywords: Podocyte